Importance of Organizational Culture and Leadership on Employee Performance: Why Organizational Culture is Important? - Sutoro Sutoro; Bambang Niko Pasla (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2020)
Human resources are crucial in achieving their goals in large and small-scale organizations. Human resources who have a high work culture and good leadership will produce quality employee performance which will ultimately optimize the purposes of an organization/company. This study aimed to determine the effect of organizational culture and leadership on employee performance in the BPSDM Provinsi Jambi Regency. The results of this study indicate that organizational culture and leadership simultaneously significantly affect employee performance, with an F count of 120.444. and a significance level of 0,000. Organizational culture has a positive and significant effect on the performance of BPSDM Provinsi Jambi Regency employees, with a t count of 12,016 and a significance level of 0,000. While leadership influences the performance of employees, the effect is small with a t count of 1.994 with a significance level of 0.05.